From disruption to remodeling: the evolution and therapeutic prospects of Neuroimmune Regulatory Circuitry after ischemic stroke - Gao, Yikun; Chen, Qing; Tao, Rui; Han, Wenrui; Zhu, Zhanyong; Gu, Lijuan (Frontiers in Immunology, 2026)
Ischemic stroke (IS) is a leading cause of death and long-term disability globally, and the efficacy of current reperfusion therapies is limited, highlighting a significant unmet clinical need. This review reconceptualizes IS not as a mere focal brain injury but as a systemic disease driven by the catastrophic collapse of the Neuroimmune Regulatory Circuitry. This sophisticated network, normally responsible for maintaining homeostasis, undergoes a multi-level failure after stroke, beginning with pathological sensory input and culminating in a dysregulated efferent response characterized by sustained sympathetic hyperactivity and Hypothalamic-Pituitary-Adrenal (HPA) axis dysfunction. These aberrant neural commands pathologically alter the phenotype and function of peripheral immune cells, leading to a profound immune imbalance: emergency hematopoiesis generates primed, pro-inflammatory myeloid cells, while the lymphoid lineage suffers massive depletion through apoptosis and sequestration, causing severe lymphopenia. This framework unifies seemingly disparate post-stroke complications—such as Stroke-Induced Immunosuppression (SIIS) and subsequent infections, long-term cardiovascular events fueled by chronic inflammation, and cognitive decline driven by persistent neuroinflammation—as predictable outcomes of this circuitry failure. Consequently, this review argues for a paradigm shift away from single-target therapies towards an “integrative and sequential” approach to treatment. Future strategies should aim to recalibrate this entire circuit, leveraging biomarkers to overcome patient heterogeneity and applying temporally-dependent interventions that inhibit acute injury while promoting chronic repair. This provides a more rational foundation for developing effective neuroprotective and restorative therapies for stroke patients.